Clinical research Aluminium and lead abnormalities in children on haemodialysis: relationship with some medications - Elshamaa, Manal F.; Sabry, Samar; Mokhtar, Inas; El-Saaid, Gamila S.; Raafat, Mona; Abd-El Haleem, Dalia A. (Archives of Medical Science, 2010)
Introduction: The determination of toxic elements in the biological samples of human beings is an important clinical procedure. This study was performed to investigate the prevalence of abnormal blood contents of 2 trace elements (TEs), aluminum (Al),and lead (Pb) in hemodialysis (HD) patients and to analyze their relationship with the medications, such as CaCO3, Ca acetate, 1,25-dihydroxy vit. D3, and erythropoietin (EPO), as well as hematocrit level. Material and methods: We included 43 patients on maintenance HD and they had continued the previously mentioned medications for at least 3 months. None of the patients were on Al containing phosphate binding agents. Results: Serum aluminum and lead levels were significantly increased than in the healthy controls, but levels of both of them were far below toxic values. Male patients had higher mean levels of lead than did females. A strong positive correlation was found between serum Al and serum Pb levels among patients (r = 0.075, p = 0.0001).The serum level of Pb was positively correlated with the serum albumin in HD patients (r = 0.45, p = 0.03). Both serum aluminium and lead levels positively correlated with the EPO dose taken by the patients (r = 0.77, p = 0.0001 and r = 0.67, p = 0.0001 respectively). Conclusions: The blood level of trace metals of these HD patients was not related to their medications except for the EPO dose. However, caution must be exercised in interpreting this result as dose and duration of medication may play an important role. Al and Pb over load may be considered from the causes of inadequate response to epoetin therapy.